Influence of Heart Rate on Quality of Life in Patients With Chronic Atrial Fibrillation - Jaber, Jefferson (Clin Cardiol, 2010)
BACKGROUND: Current criteria for rate control in atrial fibrillation (AF) treatment are empirical and based on a small amount of scientific data. HYPOTHESIS: This study was designed to analyze the influence of heart rate (HR, measured by the 6‐minute walk test [6MWT] and 24‐hour Holter monitoring) on quality of life (QoL). METHODS: A total of 89 male patients with chronic atrial fibrillation (AF) and resting HR < 90 bpm were included. QoL (assessed by the Short Form‐36 Health Survey [SF‐36] questionnaire) was compared among 3 groups of patients classified by HR testing results: group 1 had HR ≤ 110 bpm on 6MWT and ≤ 80 bpm on Holter monitor; group 2 had HR in the target area by 1 but not both tests; and group 3 had HR > 110 bpm on 6MWT and > 80 bpm on Holter monitor. RESULTS: There were significant differences among the 3 groups in physical and mental component summary scores (285.9 ± 73.9; 276.6 ± 80.8; 230.3 ± 91.0, P = .035; and 319.8 ± 70.2; 294.7 ± 76.0; 255.0 ± 107.1, P = .026, respectively). When the methods were analyzed separately, there was a significant difference on QoL in physical and mental summary scores in patients with maximal HR ≤ 110 bpm on 6MWT in comparison with HR > 110 bpm (P = .04 and P = .01, respectively) and in the physical summary score in patients with average HR ≤ 80 bpm on Holter monitor in comparison with HR > 80 bpm (P = .02). CONCLUSIONS: Holter monitoring and 6MWT should be performed as complementary methods to better predict QoL. Copyright © 2010 Wiley Periodicals, Inc.